Identification and phylogenetic characterization of novel hunnivirus recombinant strains in cattle from Guangxi, China - Zhang, Guangxin; Luo, Yuhang; Li, Jiajie; Cui, Chang; Ouyang, Kang; Chen, Ying; Wei, Zuzhang; Qin, Yifeng; Dong, Qingting; Pan, Yan; Huang, Weijian (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionHunnivirus (HuV), a member of the Picornaviridae family, is a single-stranded RNA virus associated with gastrointestinal issues in animals and poses potential zoonotic risks. While HuV has been detected in various animals, its prevalence and genetic characteristics in cattle remain poorly understood.MethodsFrom 2021 to 2023, we collected 1,017 fecal samples from cattle across Guangxi, China, and analyzed them for HuV using RT-PCR. Phylogenetic and sequence analyses were conducted to assess the virus’s genetic diversity and potential recombination events. Additionally, five HuV-positive samples were selected for whole-genome amplification and sequencing.ResultsThe overall prevalence of HuV was 3.05%, with significantly higher detection rates in diarrheic cattle (9.59%) compared to healthy cattle (2.54%). Regional prevalence varied, with the highest in Liuzhou (5.66%) and the lowest in Nanning (1.51%). Phylogenetic analysis identified a novel recombinant strain with distinct evolutionary patterns in the P3 genomic region. Sequence analysis revealed low homology in the VP1 and P1 regions compared to known genotypes, suggesting the classification of these strains as a new genotype. Additionally, the 5’ untranslated region (5’UTR) analysis confirmed the presence of type II Internal Ribosome Entry Sites (IRES), showing up to 91.8% nucleotide similarity with human parechovirus HPeV-3.DiscussionThese findings reveal significant genetic diversity and regional adaptation of HuV in cattle populations. The virus is associated with gastrointestinal symptoms, especially in areas with suboptimal farming conditions, and exhibits a potential for zoonotic transmission. This study provides a foundation for further research into the virus’s pathogenicity and zoonotic risk, highlighting the need for continued surveillance to monitor its spread and evolution.